(untitled) (Bulletin of the International Association for Paleodontology, 2023)
Taurodontism is a dental condition characterized by an abnormality in the tooth root formation, believed to be caused by defects in the invagination of the Hertwig epithelial sheath during root development. It is characterized by an enlarged, apically displaced pulp chamber, short roots, and a lack of constriction at the enamel-cementum junction. Taurodontism is classified into three degrees: hypo-, meso- and hypertaurodontism. The data was collected by measuring the height of the pulp chamber in relation to the length of the pulp chamber roof to the apex of the longest root in multirooted teeth. In this study, 1,000 panoramic radiographs (PAN) from a dental practice in Upper Austria were evaluated according to the classification of Shifman and Chanannel (1978). Hypotaurodontism was not recorded. Among the subjects evaluated, 5.9% were affected by taurodontism, and the prevalence of taurodontic teeth was 1.4%. It was found that slightly more women than men exhibited the presence of taurodontism. Mesotaurodontism was identified in 43 subjects (4.3%), hypertaurodontism in eight subjects (0.8%), and both forms were present in eight cases (0.8%). The anomaly occurred significantly more frequently in the maxilla than in the mandible. The prevalence of taurodontism varies considerably worldwide due to several factors: the use of different classifications, sample sizes, variable inclusion and exclusion criteria, and population genetic reasons. Clinically, taurodontism complicates procedures such as extractions, endodontic, prosthodontic, periodontal and orthodontic treatments, which underscores its relevance in dental practice.